Aid, Economic Freedom, and Growth - Heckelman, Jac C. (2012)
Foreign aid has often been intended by donors to entice recipient nations into policy and institutional reforms favorable to private sector economic development. In this study, we investigate the relationship between aid and changes to economic freedom in recipient nations over the 1990-2000 decade. The evidence is mixed. In general, we find that foreign aid has no significant effect on economic freedom overall. However, using a hedonic approach on the different categories of economic freedom, we find that aid has still managed to contribute toward a policy and institutional environment favorable to growth, as the different categories of economic freedom improved by aid more than offset those which are harmed by aid, in terms of their impact on growth.